PENGELOLAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - dimas hariyanto; muhsin julianto; mutia kholisah; anggi prastika sari; Indang Setia Ningsih; Ami Latifah (UNISAN JURNAL, 2023)
The teacher is a figure who carries responsibility for realizing the goals of National Education, as explained in Law Number 20 of 2003 concerning the National Education System . The aim of this research is to describe the management of Islamic Religious Education learning at SMP IT Nurul Hikam. This research method uses a qualitative descriptive method. Data was collected by means of interviews, observation and documentation. Research subjects: School Principal, Curriculum Representative, Islamic Education Teacher and Students. The results of this research are that Islamic Religious Education teachers at the beginning of the school year have prepared learning tools, implementation of Islamic Religious Education teacher learning using various methods and classroom management, evaluation of learning, including cognitive, affective and psychomotor, problems and solutions, PAI teachers hold MGMP Islamic education